Restriction on State Sovereignty and Refocus on International Human Rights as the New Trend of International Concerns - Adedara, Vincent O. (ABUAD Private and Business Law Journal, 2018)
This paper briefly discusses the overlapping and often overarching principles of state sovereignty, human rights and international concern whilst drawing on the examples of the Nicaragua Case, The East Pakistan 1971 Massacre, the Australian-run detention centre on Papua New Guineas Manus Island among others to illustrate several tensions between traditional sovereignty versus human rights principles. This paper proceeds on a discourse of the colossal conundrum created when self-assumed intervention of strong countries over the weaker nations become unguarded as a result of deviation from absolute sovereignty. The aim of this paper with doctrinal methodological approach therefore is to decipher the fact that state sovereignty is no longer absolute due to the principle of international concerns, human rights, environmental protection, humanitarian intervention, inter generational equity etc. The paper makes several recommendations and concludes that the prevalence of human rights has led to a change in the nature of traditional Sovereignty to give rooms for both political and economic interventions.